Deoxygenation of benzaldehyde over CsNaX zeolites - Peralta, María Ariela (2009)
The deoxygenation of benzaldehyde to benzene and toluene was investigated on basic CsNaX, and NaX zeolite catalysts. It was observed that as-prepared CsNaX, containing Cs in excess, displays high activity for direct decarbonylation of benzaldehyde to benzene. However, in parallel with the decarbonylation reaction, condensation of surface products occurs. Therefore, the lower pore volume of catalyst having excess Cs leads to lower catalyst stability. Decomposition of surface condensation products results in further evolution of benzene and toluene. It is observed that gas-phase H2 can play an important role by reducing the residence time of surface intermediates, thus decreasing the amount of condensation products that accumulate and lead to catalyst deactivation. Hydrogen transfer to the condensation surface products accelerates the decomposition of these condensation compounds primarily into toluene. NaX catalyst and washed CsNaX do not exhibit a high initial activity for direct decarbonylation, but rather operate via formation of surface condensation products which subsequently decompose yielding benzene and toluene. The residual acidity present in NaX catalysts causes a faster deactivation for this catalyst than for those containing Cs.